Intra-night optical polarization monitoring of blazars - Polychronakis, Aristeidis; Liodakis, Ioannis; Glykopoulou, Anastasia; Blinov, Dmitry; Agudo, Iván; Jorstad, Svetlana G.; Agís-González, Beatriz; Capecchiacci, Sara; Floris, Alberto; Kielhmann, Sebastian; Kypriotakis, John A.; Langis, Dimitrios A.; et al. (EDP Sciences, 2026)
Blazars are known for their extreme variability across the electromagnetic spectrum. Variability at very short timescales can allow us to discriminate between competing models. This is particularly true for polarization variability, which allows us to probe particle acceleration and high-energy emission models in blazars. Here we present results from the first pilot study of intra-night optical polarization monitoring conducted using RoboPol at the Skinakas Observatory; these results are supplemented by observations from the Calar Alto, Perkins, and Sierra Nevada observatories. Our results show that while variability patterns can vary widely between sources, variability on timescales as short as minutes is prevalent in blazar jets. The amplitudes of the variations are typically small, a few percent for the polarization degree and less than 20° for the polarization angle, pointing to a significant contribution to the optical emission from a turbulent magnetic field component. The overall stability of the polarization angle over time points to a preferred magnetic field orientation.